Effectiveness of Demonstration in Snake Bite First Aid in Farmer Groups - Fernanda, Edo Boy; Suhariyati, Suhariyati; Aris, Arifal; Rahmawati, Shinta Alifiana (Universitas Muhammadiyah Lamongan, 2023)
Introduction: Snake bites are a globally recognized emergency that can cause death and occur frequently, especially in tropical areas where farmers live. This research aims to analyze the effectiveness of demonstrations on farmer groups' knowledge about snake bite first aid.Method: Pre-experimental research design, one group pre-test post-test. The research sample was 65 members of farmer groups using a simple random sampling technique. The independent variable from this research is health education using the demonstration method and the dependent variable from research is knowledge about snake bite first aid. Data was taken using a knowledge questionnaire, analyzed using the Paired T test, CI = 95%Results: The results of data analysis were p=0.000<0.05, meaning that there was an influence of the demonstration method on the level of knowledge of farmer groups in providing first aid for snake bites.Conclusion: Health education using demonstration methods can provide changes to farmer groups' knowledge about snake bite first aid. It is hoped that farmer groups can apply the knowledge gained when there are snake bite victims in the field. Keywords: demonstration; farmers; first aid; snakebite